THE RELATION OF INTERIOR SPACES WITH URBAN CONTEXT - Patel, Tulsi N. (International Journal of Research -GRANTHAALAYAH, 2018)
Space, it is the area provided for particular purpose. Space can be two dimensional, three dimensional or multi. The perception of a space is known by its functionality and quality. Space does not define the use or behavior. Space can be identified as interior, exterior, common, transition; public, personal etc. 90 percent of our daily lives are spent inside. That is our experience of the city – moving from one interior to another. So our remit is to improve the quality of life for citizen, focusing on the quality of interior spaces.